Pengaruh Jenis Varietas dan Biochar terhadap Pertumbuhan dan Hasil Tanaman Wortel di Tanah Berpasir - Akbar Makkulau; Pienyani Rosawanti; Hariyadi; Muh. Azhari (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The purpose of this study is to analyze and test the influence of carrot varieties, Biochar types and treatment interactions on the growth and yield of carrots in sandy soils. This study used a factorial Group Random Design (RAK) consisting of two treatment factors as many as 3 (three) groups. Treatment factor I is a type of carrot variety (W) consisting of 2 levels, namely New Kuroda; Brastagi and Treatment Factor II are types of biochar (B) which consist of 5 levels, namely control; palm oil blank farm; oil palm shell; rice husk; nyamplung bark grouped into 3. The results of the study showed that the variety had a very real effect on plant height, wet crown weight and harvest index and had a real effect on the number of leaves, the diameter of the base of the bulbs, and the fresh weight of the bulbs. The treatment of the type of biochar has a real effect on the height of the plant and the number of leaves. The treatment interaction had no significant effect on the observation of plant height, number of leaves, diameter of the base of the bulbs, bulb length, fresh weight of the bulbs, wet weight of the crown, sweetness level and harvest index. Effective treatment in biochar carrot plant research that shows that it is effective is used rice husks and nyamplung peels.